2001
DOI: 10.1007/s001090100250
|View full text |Cite
|
Sign up to set email alerts
|

Three novel mutations in the RET proto-oncogene

Abstract: Medullary thyroid carcinoma (MTC) occurs as a sporadic tumor or in connection with inherited cancer syndromes of multiple endocrine neoplasia type 2 and familial MTC. Missense RET proto-oncogene mutations and small in-frame deletions are found in most of the cases. In a significant amount of sporadic MTC cases somatic mutation at codon 918 (exon 16), or at codons 609, 611, 618, 620 (exon 10), or codons 630, 634 (exon 11) appear. We report here on three new somatic cell missense mutations of the RET proto-oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
1
6
0
4
Order By: Relevance
“…3C). Consistent with this, mutations of serine 922, to either phenylalanine or proline, have been detected in sporadic medullary thyroid carcinoma (37,38), indicating that mutations of this residue may also be transforming in vivo. Conversely, whereas I913A and Y928A mutants retained some ability to autophosphorylate and bind substrate, they did not promote growth in soft agar assays, even on ligand stimulation (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…3C). Consistent with this, mutations of serine 922, to either phenylalanine or proline, have been detected in sporadic medullary thyroid carcinoma (37,38), indicating that mutations of this residue may also be transforming in vivo. Conversely, whereas I913A and Y928A mutants retained some ability to autophosphorylate and bind substrate, they did not promote growth in soft agar assays, even on ligand stimulation (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Somatic RET mutations at codons 608, 611, 618, 629, 630, 634, 639, 641, 918, or 922 are found in approximately 25% of patients with sporadic MTC, with mutations at codon 918 occurring most frequently (81)(82)(83)(84)(85)(86)(87)(88)(89). As with germline 918 mutations, the somatic 918 mutations are associated with aggressive MTC behavior (9,90).…”
Section: Germline and Somatic Mutationsmentioning
confidence: 99%
“…A few patients with MEN 2B may also have a mutation in colon 883 (intracellular tyrosine kinase domain, exon 15) (10,95,(113)(114)(115). Several authors have previously described codon 922 in association with MEN 2B; however, these reports included patients with either somatic codon 922 mutations present only within tumor cells or a compound heterozygous genotype with germline codon 918 and 922 mutations (84,(116)(117)(118). Kitamura et al (118) found that the codon 922 mutation, which was maternally inherited (the codon 918 mutation occurred de novo in the patient), did not cause features of MEN 2B in the patient's mother and, therefore, concluded that the codon 922 mutation is unlikely to seriously affect the function of RET and seems not to confer a deleterious effect.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Somatic RET mutations are found in a fraction of sporadic MTCs and, rarely, in pheochromocytomas. Mutation at the codon 918 or at the cysteine codons 609, 611, 618, 620, 630, 634 appear in a significant amount of sporadic MTC cases and recently three new somatic missense mutations (at codons 639, 641, and 922) of the RET proto‐oncogene associated with sporadic MTC have been described (Kalimin et al, 2001).…”
Section: Sporadic Mtcmentioning
confidence: 99%